Social Entrepreneurship - Just Add Water - Kotálová, Radka (2011)
This work deals with the phenomenon of social entrepreneurship in the context of the African continent. First of all, it concentrates on the situation in Africa with respect to water and then on the importance of property rights in the resolving of the situation. Subsequently it discusses one of the common attempts to solve the water crisis, i.e. aid. The second part of the thesis is concerned with social entrepreneurship only. Firstly, from the theoretical point of view (definition, typology) and secondly, from the practical point of view (case studies of enterprises that are trying to push Africa closer to achieving the Millennium Development Goal of halving the proportion of people without access to safe drinking water).